Közép- és Kelet-Európa átalakulási, integrációs dilemmái és a mezőgazdaság fenntartható fejlesztése - Somogyi, Sándor (Tér és Társadalom, 1996)
It is characteristic of Eastern Europe where we belong that the conditions swing between harmonisation and disharmonisation and integration-disintegration. Never-ending combats of interests and counter-interests are taking place before us and we cannot avoid being part of it. In our region the need for forced development, economic activity to the detriment of the natural resources (that is typical of the less developed region) and environmental pollution ínevitably appeared. Our keeping up with the developed countries is thus a double burden. It is not only the need for development that takes the resources that we have but also environmental investments have to be carried out in order to make the national economies Euro-conform. In the countries of the region, agricultural production plays a relatively more important role than in the EU, considering the size of agricultural areas and the contribution of this sector to GDP and employment. Ecological problems are continuously on the surface: in developed countries because of the splendid quality of life, in developing countries because of quantitative development and the necessity of transformation. Transformation is presently taking place in the region, and a new phase of technical-technological development is gaining ground. We have to emphasise, however, that we cannot rely exclusively upon analogy – comparisons with the solutions of the past but we have to build on new development concepts. We must not think in terms of technologies developed in the past period, which neglected the problems of land, raw material and energy, but we have to introduce new technologies which take the economical use of land, energy and raw materials into consideration. In addition, they help the breaking down of wastes, thus they are not linear but circular, similarly to the processes of Nature.